Peran Telepon Operator dalam Meningkatkan Kualitas Pelayanan di Aryaduta Menteng - Khansa Maulida; Nila Rifai (Bogor Hospitality Journal, 2025)
This study aims to examine the role of telephone operators in improving service quality at the Aryaduta Menteng Hotel. The background of the study is based on the importance of initial communication via telephone as a first impression that influences guest perceptions of the overall quality of hotel services. This study uses mixed methods with an exploratory sequential design. The initial stage was carried out qualitatively through in-depth interviews with hotel staff, such as operators, receptionists, and concierges, to gain a deeper understanding of the role of operators. The qualitative findings were then used as the basis for compiling research instruments which is questionnare in the quantitative stage, which were distributed to hotel guests to determine their level of satisfaction with operator services. The results of the study indicate that telephone operators have a strategic role in creating fast, friendly, and effective service. Operators not only carry out technical tasks of receiving and forwarding calls, but also build polite and empathetic interpersonal communication, and maintain coordination between departments so that guest complaints or requests can be handled quickly.